2010
DOI: 10.3813/aaa.918330
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Sound Field for Floor Impact Sounds Generated by Heavy/Soft Impact Sources

Abstract: Field measurements of floor impact sounds at lowf requencies give poor repeatability due to spatial sampling problems. In this study,t he spatial distribution of heavy-weight impact sound pressure levels wasi nvestigated by field measurements using heavy/soft impact sources, which have been specified as as tandard heavy-weight impact source in 140-11. The results of the present study showed that the vertical and horizontal distribution of measured sound pressure levels showed asignificant room mode effect at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
(13 reference statements)
0
3
0
2
Order By: Relevance
“…Among the 14 participants, 10 mentioned footsteps, which agreed with the previous findings that footsteps were the most frequent noise source in apartment buildings [2,25,26 Lightweight impact noise sources were also mentioned by the participants, although less frequently compared to heavyweight impact sources. This was because, unlike heavyweight impact noise, the dominant sound energy produced by lightweight impact noise sources can be easily reduced by acoustical treatments such as floor coverings and resilient isolators [27] and road traffic noises found that the noise was less tolerable in the early morning and evening [28]. Most of the participants of the present study also reported that they had heard floor impact noise at night or in the morning.…”
Section: Resultsmentioning
confidence: 62%
“…Among the 14 participants, 10 mentioned footsteps, which agreed with the previous findings that footsteps were the most frequent noise source in apartment buildings [2,25,26 Lightweight impact noise sources were also mentioned by the participants, although less frequently compared to heavyweight impact sources. This was because, unlike heavyweight impact noise, the dominant sound energy produced by lightweight impact noise sources can be easily reduced by acoustical treatments such as floor coverings and resilient isolators [27] and road traffic noises found that the noise was less tolerable in the early morning and evening [28]. Most of the participants of the present study also reported that they had heard floor impact noise at night or in the morning.…”
Section: Resultsmentioning
confidence: 62%
“…Some authors concluded that the floor impact evaluation performed using a tapping machine does not accurately emulate the characteristics of human footsteps or low frequency impact noise (SHI;JOHANSSON;SUNDBACK, 1997;WARNOCK, 2000;NEVES E SOUZA;GIBBS, 2001;JEON, 2001;SCHOLL, 2001;BRADLEY, 2004;JEON et al, 2004;SATO, 2008;KIM et al, 2009;SCHOENWALD et al, 2010;SCHOENWALD;ZEITLER;NIGHTINGALE, 2010;YOO, 2010). Shi, Johansson and Sundback (1997) carried a study to determine the correlation between human impact noise and other alternative impact sources, such as sand balls and sand bags, tires and the tapping machine.…”
Section: Introductionmentioning
confidence: 99%
“…As medições foram consideradas in situ, uma vez que as salas do laboratório para a realização desse experimento não atendem a todos os critérios da norma ISO 140-6. Como a fonte pera não é normalizada, os experimentos foram realizados de acordo com os métodos da norma ISO 10140-5:2010 e recomendações de estudos sobre ruído de impacto em pisos e fontes tipo bola (SHI; JOHANSSON; SUNDBÄCK, 1997;WARNOCK, 1998WARNOCK, , 1992WARNOCK, , 2000JEON, 2001;JEON et al, 2004;BRADLEY, 2004;SATO, 2008;KIM et al, 2009;YOO et al, 2010;SCHOENWALD et al, 2010). As medições com a pera foram efetuadas utilizando-se um mecanismo que permitiu segurá-la e soltá-la a 1 m do piso, conforme recomenda o Anexo F da ISO 10140-5 (INTERNATIONAL..., 2010d).…”
Section: Figura 1 -Fontes Sonoras Geradoras De Ruído De Impactounclassified
“…Embora existam muitos esforços para reduzir o ruído de impacto nos pisos das construções, ainda não foi definido um método eficiente que seja capaz de isolar o ruído de impacto causado nas baixas frequências, isto é, de 20 a 200 Hz. Um dos aspectos que contribuem para isso é o fato da própria máquina de impactos padronizada ser deficiente para excitar essa faixa de frequência (SHI; JOHANSSON; SUNDBÄCK, 1997;WARNOCK, 1998WARNOCK, , 1992WARNOCK, , 2000JEON, 2001;JEON et al, 2004;BRADLEY, 2004;SATO, 2008;KIM et al, 2009;YOO et al, 2010;SCHOENWALD et al, 2010.;SCHOENWALD;ZEITLER;NIGHTINGALE, 2010;NEVES E SOUSA;GIBBS, 2011;CABEÇAS, 2011). Outro fator a ser ressaltado é que as frequências centrais, em banda de terço de oitava para análise, estabelecidas nas normas ISO (INTERNATIONAL..., 2010a(INTERNATIONAL..., , 2010b(INTERNATIONAL..., , 2010c(INTERNATIONAL..., , 2010dSHI;JOHANSSON;SUNDBÄCK, 1997), são superiores a 100 Hz e sabe-se que a audição humana consegue detectar sons entre 20 e 20.000 Hz.…”
Section: Introductionunclassified